Answer:
Explanation:
If the numerator is 7 less than its denominator, than the original number in terms of x is
. If we triple the numerator, the expression to do this is 3(x - 7); if we increase the denominator, the expression to do this is x + 13. Putting that together along with the fact that after we do this manipulation the new number is 3/2:
and distribute:
and cross multiply to get:
2(3x - 21) = 3(x + 13) and
6x - 42 = 3x + 39 and
3x = 81 so
x = 27. Subbing 27 for x into the original number:
![(27-7)/(27)=(20)/(27)](https://img.qammunity.org/2022/formulas/mathematics/high-school/exgxb9msdihf4vucpu5lbmy0q1lmo2znwt.png)